California Poly Mustangs [composite portrait, from page 4 of program] (1958)
Pictured in the portrait: Pat Lovell, T; Fred Ford, HB; Ray Porras, FB; Merle Kinsley, E; Willie Hudson, G; Benny Martin, HB; John Panagakis, Q; Denis Wagner, G; Joel Copeland, C; Bill Jones, HB